The Effect of Self-Efficacy on Entrepreneurial Intention with the Mediation Variables of Attitude Towards Behavior, Perceived Behavioral Control and Subjective Norm (a Study on the Master’s of Management Students at Universitas Ciputra Surabaya) - Putra, Briandy; Antonio, Tony (KnE Social Sciences, 2021)
Entrepreneurship education is one of the national programs to boost the number of entrepreneurs in the country. The success of creating educated entrepreneurs depends on several factors such as the curriculum, mentors, the method and the readiness of the participant. The intention to become an entrepreneur cannot be separated from the individual’s self-efficacy. This research examined the effect of master’s students’ self-efficacy on their entrepreneurial intention, with the mediation of the Planned Behavior Theory variables. The sample included 134 master’s students out of the total of 203. All had been conducting business for at least six months and were recruited through purposive sampling. A 1-5 Likert scale questionnaire was given to the respondents in print and through Google Forms. Quantitative data analysis was done using smart-PLS version 3. Two of the three variables of the Planned Behavior Theory were significant as mediators of self-efficacy, namely attitude toward behavior and subjective norm. Perceived behavioral control did not have an effect on self-efficacy and entrepreneurial intent through mediation. Keywords: self-efficacy, theory of planned behavior, attitude toward behavior, perceived behavioral control, subjective norm, entrepreneurial intention